The role of iodine in thyroid function and iodine impact on the course of Hashimoto’s thyroiditis - review - Malinka, Zuzanna; Gmitrzuk, Julita; Wiśniewska, Katarzyna; Jachymek, Anna; Opatowska, Martyna; Jakubiec, Joanna; Kucharski, Tomasz; Piotrowska, Marta (Quality in Sport, 2024)
Introduction: Iodine is one of the most important micronutrients necessary for the proper functioning of the thyroid gland. It is an essential component of thyroxine and triiodothyronine, hormones produced and secreted by the thyroid gland. Severe iodine deficiency impairs thyroid hormone synthesis and can lead to gland enlargement. This deficiency results in various disorders collectively termed iodine deficiency disorders. Not only iodine deficiency but also excess iodine intake can be harmful and affect thyroid function. Doses of iodine above physiological levels can result in both hypothyroidism and hyperthyroidism. Numerous studies have linked chronic high iodine intake to an increased frequency of autoimmune thyroiditis. This review examines the mechanisms of iodine regulation and the role of excess iodine can play in the development of Hashimoto’s thyroiditis. Aim of the study: The aim of the study is to present and summarize the role of iodine in thyroid function and its impact on the course of Hashimoto’s thyroiditis. This review explains the potential increased risk of thyroid autoimmune disorder connected with iodine over-supplementation. Materials and Methods: For this current literature review, the important studies published from 1986-2024 in PubMed database was searched. The literature available in the PubMed database was reviewed with the following keywords: iodine, Hashimoto’s thyroiditis, autoimmune thyroiditis. Conclusion: Iodine is crucial for thyroid health and fetal development, but its excessive intake can be harmful. Maintaining optimal levels of this microelement is essential to prevent both iodine deficiency and autoimmune disorders. Iodine supplementation is recommended only for pregnant and lactating women.